TAKWIL DALAM PANDANGAN MULLA SADRA - Nur, Muhammad (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
This paper seeks to explain the notion of â€œta'wÄ«lâ€ in the view of Mulla Sadra. There are several important issues that would be discussed. What is ta'wÄ«l ? Is it distinguished from interpretations either contrast to the exoteric meaning? Why do we need ta'wÄ«l? Is the interpretation alone is enough? How does the process?. It would also attempt to explain the three important issues of ta'wÄ«l; first, the definition of ta'wÄ«l according to Mulla Sadra. Second, to explain the foundation of ta'wÄ«l. Third, to describe the two methods that might be used in ta'wÄ«l. For Sadra, as internal meaning, ta'wÄ«l does not eradicate or invalidate the outward meaning of the verse, rather it is the complement aspect. It becomes evident that sacred texts (al-Qur'an and hadÄ«th) have different levels of meaning. Thus, in the process of ta'wÄ«l, there are two important methods that might be used, i.e., the sufistic method and the method of the outward-inward meaning.